Connecting: Newsletter Highlights & Achievements from 2024–2025 | Activity Report - Agapiou, Athos (My University, 2026)
Welcome to the first issue of the CONNECTING Project Newsletter. This issue provides an overview of key project milestones, events, demonstrations, and recognitions from 2024 to 2025. Stay up-to-date with our progress in digital cultural heritage, geospatial technologies, and collaborative research activities.